Serum Brain-Derived Neurotrophic Factor, and Plasma Catecholamine Metabolites in People with Major Depression: Preliminary Cross-Sectional Study - Yoshimura, Reiji; Kishi, Taro; Atake, Kiyokazu; Katsuki, Asuka; Iwata, Nakao (Frontiers in Psychiatry, 2018)
Background: There are complicated interactions between catecholaminergic neurons and brain-derived neurotrophic factor (BDNF) in the brain. However, no reports have addressed the relationship among 3-methoxy-4-hydroxyphenylglycol (MHPG), homovanillic acid (HVA), and BDNF in the blood. Objective: This paper sought to investigate correlations between serum BDNF and plasma levels of MHPG and HVA in major depressive disorder (MDD) patients. Materials and methods: A total of 148 patients (male/female 65/83, age 49.5±12.1 years old) who satisfied criteria for MDD based on the Diagnostic and Statistical Manual of Mental Disorders IV (DSM-IV) were enrolled in the present study. Plasma levels of MHPG and HVA were analyzed using high-performance liquid chromatography, and serum BDNF was measured using ELISA. Results: No interactions were observed between plasma HVA levels (mean±s.d.= 4.5±1.5ng/ml) and age(, sex, HAMD scores, or serum BDNF levels (mean±s.d.= 9.8±2.9ng/ml). No correlations were not also observed between plasma MHPG levels (mean±s.d.= 5.9±2.1ng/ml) and age, sex, the HAMD17 scores(mean±s.d.= 22.2±2.9ng/ml), or serum BDNF levels. Serum BDNF levels were negatively associated with HAMD17 scores. Conclusion: The results suggest that there are no significant correlations between catecholamine metabolites and BDNF in the blood for MDD patients.